Symmetric and Asymmetric Causality Analysis of the Relationships between Sectoral Confidence Indices and ISE Sector Indices - İsmail CANÖZ (Yönetim ve Ekonomi, 2019)
In this study, sector-based relationships between confidence indices and stock exchange indices are investigated for January 2011-June 2019 period. Monthly data sets on financial service confidence index, service confidence index, construction confidence index, retail trade confidence, and stock market indices are firstly analyzed by Hacker and Hatemi-J (2006) test. Secondly, they are examined in terms of asymmetric causality relationship with Hatemi-J (2012) test. According to the findings obtained as a result of the tests; the existence of a symmetric causality relationship between the sectoral confidence indices and related Istanbul Stock Exchange (ISE) sector indices could not be identified in Turkey. However, an asymmetric causality relationship is found between these variables. In other words, while there is no direct causal relationship between sectoral confidence indices and stock market sector indices, there is a causality relationship through the components of these variables.